Efeito das micotoxinas no estresse oxidativo, parâmetros bioquímicos séricos, microbiota cecal e morfometria intestinal de frangos de corte - Liberalesso, Diogo (2021)
This research aims to evaluate the toxic effects of the main mycotoxins of interest in the Brazilian poultry industry, drawing in a single study to measure the toxic effects caused by aflatoxins, fumonisins, deoxynivalenol and T-2 toxin in cutting strips, evaluating markers of biochemical damage serums, analysis of the cecal microbiota and jejuna morphometri. Sixty male chicks kept from 1-28 days of age were used. The animals were randomly divided into 5 groups: T1 (basal diet, negative control), T2 (basal diet + 2.8 mg.kg-¹ of aflatoxins), T3 (basal diet + 120 mg.kg-¹ of fumonisins), T4 (basal diet + 50 mg.kg-¹ deoxynivalenol) and T5 (basal diet + 3 mg.kg-¹ toxin T-2). The following analyzes were performed in serum biochemistry: total proteins, albumin, uric acid, cholesterol, triglycerides, calcium, phosphorus, alanine aminotransferase (ALT) and aspartate aminotransferase (AST). In the plasma of the poultrys used in the study, thiobarbituric acid reactive substances (TBARS), carbonyl protein (CARB) and total antioxidant capacity (TAC) were measured. A jejunum fragment was collected to assess the height of villi and crypt depth. From the cecal content of these animals, cultures and counting Lactobacillus spp. and total coliforms. The presence of aflatoxins in the diet of poultrys promoted a decrease in serum levels of total protein, albumin and cholesterol. Fumonisins promoted an increase in AST activity. The addition of T-2 toxin in the poultry diet led to an increase in ALT activity and a decrease in total protein levels. Deoxynivalenol did not change the biochemical parameters in the present study and uric acid and triglyceride levels were not altered with the presence of mycotoxins tested in the diets. The height of the villi was modified with the presence of aflatoxins and fumonisins in the feed and deoxynivalenol was able to decrease the depth of crypts and thus alter the villous/crypt ratio. The total coliform count in the cecum of birds was increased in all treatments contaminated with mycotoxins, however the count of Lactobacillus spp. was not changed in the present study. The level of TBARS and CARB in the animals' plasma did not change with the presence of mycotoxins in the diets, but the TAC was increased in treatments with aflatoxins and deoxynivalenol. The results show the effects of mycotoxins on serum biochemical parameters, oxidative stress, as well as the ability of these toxic metabolites to affect the intestine and interact with the microbiota of this organ.